Local Politics Influenced Performance For Local Companies? : A Story From Surabaya - Wiliam Santoso; Jeslyn Livia Soedewa; Jonathan Edward Surya; Michelle Michiko Tjondro; Michael Brandon Tjahyadi (Universitas Pendidikan Indonesia, 2023)
Abstract – The purpose of this research is to determine the differences of financial performance and market performance before, as at, and after direct election for local government executive on 2015. This research picks 30 Surabaya based listed companies as samples based on purposive sampling method with several criteria during 2014-2016. Method of hypothesis testing uses multivariate analysis of variance (manova) and analysis of variance (anova) test with three groups of periods, which are before, as at, and after the direct election for local government executive on 2015. The results show that there is no significant financial performance of local based company in Surabaya caused by direct local government election on 2015 measured by current ratio, working capital turnover ratio, debt to equity ratio and return to equity ratio. The market performance test also shows that there is no significant market performance of local based company in Surabaya caused by direct local government election on 2015 measured by abnormal return. Investors are advised to be more focus on the company’s financial performance.